Clinically oriented anatomy - Moore, Keith L. 4 0 16; Dalley, Arthur F.; 5 (Philadelphia : Lippincott Williams & Wilkins, 1999)
An anatomy text, featuring over five hundred color illustrations, focusing on anatomy important in general practice, diagnostic radiology, emergency medicine, and general surgery; with medical imaging, case studies, and clinical correlations.
Includes bibliographical references and index.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Human anatomy.;Anatomy.;Human anatomy; 20; 2